Effects of early language, speech, and cognition on later reading: a mediation analysis - Durand, Vanessa N.; Loe, Irene M.; Yeatman, Jason D.; Feldman, Heidi M. (Frontiers in Psychology, 2013)
This longitudinal secondary analysis examined which early language and speech abilities are associated with school-aged reading skills, and whether these associations are mediated by cognitive ability. We analyzed vocabulary, syntax, speech sound maturity, and cognition in a sample of healthy children at age 3 years (N=241) in relation to single word reading (decoding), comprehension, and oral reading fluency in the same children at age 9 to 11 years. All predictor variables and the mediator variable were associated with the three reading outcomes. The predictor variables were all associated with cognitive abilities, the mediator. Cognitive abilities partially mediated the effects of language on reading. After mediation, decoding was associated with speech sound maturity; comprehension was associated with receptive vocabulary; and oral fluency was associated with speech sound maturity, receptive vocabulary, and syntax. In summary, all of the effects of language on reading could not be explained by cognition as a mediator. Specific components of language and speech skills in preschool made independent contributions to reading skills 6 to 8 years later. These early precursors to later reading skill represent potential targets for early intervention to improve reading.